The Influence of Leverage, Media Exposure, and Liquidity on CSR Disclosure (Empirical Study on ASR Award-Winning Companies in 2012-2020) - Aulia, Putri Raihana Nur; Setyorini, Dhyah (Universitas Pendidikan Indonesia, 2021)
AbstractThis research aims to determine the influence of (1) Leverage, (2) Media Exposure, (3) Liquidity to Corporate Social Responsibility (CSR) Disclosure in Asia Sustainability Reporting (ASR) award-winning companies. The period used in this study is 9 (nine) years from 2012 to 2020. This research is a associative causality research. The population of this research is taken from ASR award-winning companies organized by NCSR and listed on the Indonesia Stock Exchange (IDX). The samples used in this study were 108 data from 31 companies determined by the purposive sampling method. Data collection techniques with secondary data documentation sourced from the company's website, annual reports, and sustainability reports. Then, the analysis technique used is the multiple linear regression analysis techniques. The results of this study are: (1) Leverage has a significant positive effect on CSR Disclosure. (2) Media Exposure does not affect CSR disclosure. (3) Liquidity positively affects CSR Disclosure.